GAMBARAN PENGETAHUAN IBU TENTANG STATUS NUTRISI PADA ANAK USIA SEKOLAH (6-12 TAHUN) DI YAYASAN MADRASAH IKHLASIAH MEDAN - R, Maimunah (JURNAL KELUARGA SEHAT SEJAHTERA, 2018)
ABSTRACT                                                                                                          The purpose of this study is to describe the mother's knowledge about nutrition in school age children (6-12 years). The result is that the majority of respondents knowledgeable enough as many as 30 respondents (66.7%) in the age group> 30 years as many as 22 respondents (48.9%), family education largely secondary education as much as 20 respondents (44.4%), employment of family members is a housewife of 20 respondents (44.4%) of the respondents dansebagian obtain health information through electronic media as much as 25 respondents (55.6%). Keywords: Knowledge, Nutrition Status of School Children